Thrifting: Consumer Perceptions and Decisions - Angelica, Nevlin; Hasanah, Fira; Khumayah, Siti; Erawati, Dedet (Pelopor Publikasi Akademika, 2025)
The fashion industry continues to evolve in line with growing awareness of sustainability and changing economic conditions, which has led to the emergence of the thrifting business phenomenon. This study aims to analyze consumers' perceptions and purchasing decisions regarding thrift products, as well as identify the factors influencing purchasing decisions, such as price, quality, sustainability, and social and cultural aspects, to provide insights into the dynamics of the thrifting market as part of a sustainable lifestyle in the modern era. The study employs a qualitative approach using descriptive analysis and thematic data analysis of informants comprising consumers and business operators. The theory applied in this research is consumer decision-making according to Philip Kotler & Kevin Lane Keller (2009: 184). The results indicate that consumer perceptions directly influence interest in purchasing thrift products, influenced by economic factors, awareness of sustainability, and individual style preferences.